Prevalence and determinants of metabolic syndrome among the rural adult population of Puducherry - Vinayagamoorthy Venugopal; Amol R Dongre; Sumathi Saravanan (Wolters Kluwer Medknow Publications, 2019)
Background: Burden of metabolic syndrome (MS) is rising. There were many previous studies conducted in India on MS, yet it is less studied in Puducherry which has embraced modern culture and lifestyle. Hence, we aimed to study the prevalence and predictors of MS. Materials and Methods: A cross-sectional study was undertaken on a representative sample of 489 adults of age 30 years and above over the period of 18 months. MS was defined according to the International Diabetes Federation (IDF) criteria. Data on sociodemography, lifestyle characteristics, and biochemical parameters were collected by a well-trained health professional using standard methods. Generalized linear models with Poisson distribution and log link function were used to calculate the adjusted prevalence ratio (PR). Results: The prevalence of MS was 39.7% (95% confidence interval [CI]: 35.3-44.1) among the study participants. The most commonly deranged component of MS was central obesity (63.6%). Increasing age, upper socioeconomic status, low fruit intake, physical inactivity, use of refined sunflower oil (PR: 1.40, 95% CI: 1.07-1.83) for cooking, and high perceived stress (PR: 1.77, 95% CI: 1.32-2.37) were found to be associated with MS. Conclusion: The prevalence of MS in Puducherry was high as per the IDF criteria. Usage of refined sunflower oil for cooking and perceived stress was independently associated with an increased risk of MS along with other routinely studied risk factors.